Electrospun Scaffolds: Enhanced Lineage‐Specific Differentiation Efficiency of Human Induced Pluripotent Stem Cells by Engineering Colony Dimensionality Using Electrospun Scaffolds (Adv. Healthcare Mater. 12/2016). Issue 12 (22nd June 2016) - Maldonado, Maricela; Ico, Gerardo; Low, Karen; Luu, Rebeccah J.; Nam, Jin
Abstract : Electrospun scaffolds provide soft nanofibrous networks pliable by human induced pluripotent stem cells. J. Nam and co‐workers show on page 1408 that such compliant scaffolding leads to the formation of stem cell colonies with a distinctive three‐dimensional morphology. The morphological modulation resulted in the lineage‐specific differentiation, suggesting a potential means to enhance translational applications of the stem cells.